The Fickle Crowd: Reinforcement and Contradiction of Quality Evaluations in Cultural Markets - Kim, Minjae; DellaPosta, Daniel (Organization Science, 2022)
We clarify conditions under which two seemingly contradictory yet widely observed tendencies occur in cultural markets where amateur connoisseurs evaluate products—reinforcement of previous consensus and contradiction of that same consensus. We start from prior work’s insight that achieving “distinction” requires that evaluators display tastes demonstrating higher skills of discernment and standards that are acknowledged as legitimate by others. Based on this, we argue that evaluators reinforce prior evaluations of products to demonstrate that they share the same quality standards as their peers, but they selectively contradict prior evaluations by downgrading widely acclaimed products, because doing the latter makes the evaluator appear to have even more sophisticated tastes than their peers. We test this account using 1.66 million reviews from an online platform where amateur connoisseurs publicly evaluate beers. Our analyses support an endogenous model explaining why and when evaluators may contradict existing evaluations even though a group plausibly sharing the same quality standards may have established such evaluations in the first place. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2021.1556 .